OPTIMIZATION OF INJECTION MOLDING PARAMETERS TO MINIMIZE SHRINKAGE AND MAXIMIZE TENSILE STRENGTH IN THE RECYCLING PROCESS OF DISPOSABLE FACE MASKS - Widyasmoro, Irvan Bayu; Widiastuti, Indah; Estriyanto, Yuyun; Budiyanto, Khansa Qonitatillah (Jurnal Rekayasa Mesin, 2024)
Recycling used face masks into useful products is an alternative way to reduce the accumulation of medical waste during the COVID-19 period. The main objective of this study was to determine the effect of injection molding parameters of barrel temperature, molding temperature, and cooling time on tensile strength and plastic shrinkage during the recycling process of used disposable face masks. The study utilized a Design of Experiment (DoE) using the Taguchi Orthogonal L9 method. In this current study, the barrel temperatures were set at 170oC, 190oC, and 220oC. with the molding temperatures used are 45°C, 60°C, and 75°C, while the values of cooling time were 26s, 43s, and 52s. The tensile test was carried out according to the ASTM D638 type V standard for measuring the strength of materials. The findings demonstrate that the most important factor in achieving the highest tensile strength is the molding temperature, which contributes 34.54% and is best combined with a barrel temperature of 170°C, a molding temperature of 60°C, and a cooling period of 52s. By contributing 54.40% to the parameter combination of barrel temperature of 170°C, molding temperature of 45°C, and cooling time of 52s, the molding temperature becomes the most crucial factor to produce the least amount of shrinkage